When herpes zoster is not herpes: A case of statin-induced myopathy complicated by drug allergies - Hira Khalid Kareem; Muhammad Fawad Ashraf; Muhammad Shehryar; Hafsa Fayyaz; Shreyas Patil (IDCases)
Statins are commonly prescribed to reduce cardiovascular risk, but statin-induced myopathy is a leading cause for therapy discontinuation. This case report discusses a 69-year-old female with multiple comorbidities, including smoldering multiple myeloma, who presented with myalgias and a vesicular rash initially suspected to be herpes zoster due to her immunocompromised status. Elevated creatine kinase (CK) levels were noted (>9000 U/L) while the patient was on high-dose atorvastatin. Despite initial suspicions of herpes zoster, the rash’s atypical progression led to further evaluation, revealing a more complex picture. The patient had a significant history of drug allergies, complicating the diagnosis, particularly following recent clindamycin treatment for a dental issue. After discontinuing atorvastatin and clindamycin, her CK levels improved, and subsequent testing confirmed the presence of anti-HMG-CoA reductase antibodies, establishing a diagnosis of statin-induced autoimmune necrotizing myopathy. This case underscores the importance of detailed patient histories and the need to consider drug-induced hypersensitivity reactions in immunocompromised individuals. The resolution of symptoms after stopping the offending medications emphasizes the critical role of careful monitoring and diagnosis in managing patients with complex medical backgrounds.